Pengaruh Transparansi, Asimetri Informasi, dan Partisipasi Masyarakat terhadap Potensi Kecurangan Dana Desa - Delvira Eka Selvia; Fefri Indra Arza (Universitas Negeri Padang, 2023)
This research aims to examine the effects of transparency, information asymmetry, and community participation on the potential for fraud in village funds. The research includes the category of causality. The population of this research is 12 Nagari in Sutera sub-district, Pesisir Selatan regency. This study type is total sampling and the sample of this research makes all the population as samples. For the data source used is in the form of primary data. Data collected through questionnaires. The results obtained from this study are (1) Transparency has no effect on the potential for fraud in village funds. (2) Information asymmetry has a positive and significant effect on the potential for fraud in village funds. (3) Community participation does not effect the potential for fraud in village funds.